Форми авторської рефлексії жанру послання в текстах української адресованої лірики ХІХ–ХХ ст. (Літератури світу: поетика, ментальність і духовність, 2016)
This article deals with the analysis of the addressed lyrics artistic phenomenon as supergenre formation which includes three poetic genres – message, dedication, poetic letter. Authors genre reflection forms in the Ukrainian addressed lyrics texts investigated, its communicative-dialogic organization, artistic factors defining semantics of its addressing.
Keywords: метажанр; жанрова рефлексія; діалогічність; адресована лірика; послання; присвята; віршований лист